Pengaruh Masa Panen Madu Lebah pada Area Tanaman Kaliandra (Calliandra calothyrsus) terhadap Jumlah Produksi Kadar Air, Viskositas dan Kadar Gula Madu (Faculty of Animal Science Universitas Brawijaya, 2016)
The purposes of this research were to investigate the difference of harvesting time on honey production, viscosity, moisture and sugar content, as well as identifying the best harvesting time.The material used in this research was honey from Calliandra plantation. The method used was experimental design using Completely Randomized Design (CRD) with 3 treatments and 5 replications. The treatment consisted of harvesting time on day 11 P1on day 14 P2, and on day 17 P3. Data obtained were analyzed by ANOVA and continued by LSD test. The results showed that the treatments had significantly effect (P<0.01) on honey production, viscosity, water and sugar content. On P1, production obtained was 1.59 L/colony/harvest, while 0.72 and 0,26 from P2 and P3, respectively. Moisture of P1, P2, P3 respectively were 22.02, 21.00, 19.48 %, respectively. Viscosity obtained was 11.43, 18.56, and 33.67 P. Sugar content were 69.46%, 70.59%, and 71.67%, respectively. In conclusion, viscosity and sugar content of honey will increase when it is harvested on day 17, but decrease when it is harvested on day 11. However, harvesting time on day 11 is the best choice for farmer due to highest production obtained, but inadequate of standard of water content, viscosity, and sugar content.